(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Background: This study was carried out to find out the seropositive of HBV, HCV, HIV, Treponema pallidum and Malarial parasite among the blood donors attended at transfusion medicine department of DMCH in 2014. Our objective is to prevent the spread of Transfusion transmissible disease through blood transfusion and awareness of mass population about TTI. Method: This study was carried out at transfusion medicine department of DMCH from 1st January 2014 to 31st December 2014.Total blood donors were 39,512.Blood donors of 18 - 60 years of both sexes were included in this study. Results: Among 39,512 blood donors relative blood donors were 32,778(82.95 %), voluntary blood donors were 6734.( 17.04% Among 39,512 blood donors , HBsAg positive 456 (1.154%), Anti HCV positive 33(.090%), Malarial Parasite positive 04 (.010), Treponema pallidum positive 87 (.220%) and positive for HIV 01(.0025%) Conclusion: Prevention of spread of TTIs should be the main goal at the current time. It is important to follow the WHO guidelines to tests every donor for HBV, HCV, HIV and Syphilis to decrease the transmission of TTIs. Anwer Khan Modern Medical College Journal Vol. 7, No. 1: Jan 2016, P 11-13